Tensile Strength, Microstructure, and Fractography Analysis of FDM 3D Printed Parts Using Self-Made PLA-Brass Filaments - Mahros Darsin,; Indra Cahyo Kuncoro,; Nasrul Ilminnafik,; R. Koekoeh Koentjoro Wibowo,; Agus Triono ,; Mohd Sabri Hussin, (International Journal of Integrated Engineering, 2026)
Manufacturing technology development has experienced various innovations, including 3D printing. The progress of 3D printing has been adopted in various fields. This study explores the innovations in manufacturing technology, particularly the advancement of 3D printing and its application in producing metal alloy filaments. The focus is on creating an innovation using PLA-brass filament, with extruder temperature, layer height, and print speed as control parameters. The objective is to distinguish the ideal combination of these 3D printing parameters to realise the greatest ductile quality. Through the Taguchi method application, the aim is to enhance product quality while reducing fabrication costs. An L4(2)3 orthogonal matrix is employed, leading to four experimental combinations replicated three times, amounting to twelve experiments overall. The data obtained from tensile testing is then analysed using Analysis of Variance (ANOVA) to determine which parameters significantly impact the test results. This study concludes that the optimal tensile strength is achieved with an extruder temperature of 230°C,  a print speed of 20 mm/s, and a layer height of 0.2 mm. The analysis also reveals that extruder temperature contributes 38.81% to the tensile strength results, followed by layer height at 17.5%, and print speed at 15.26%